Pandangan Tokoh Masyarakat terhadap Pernikahan Wanita Hamil di Luar Nikah Perspektif ‘Urf (Studi Kasus di Nagari Paninggahan Kecamatan Junjung Sirih Kabupaten Solok) - Jannah, Izatul; Rahmiati, Rahmiati (Lembaga Yasin AlSys, 2026)
The marriage of women pregnant out of wedlock has received attention in several studies, yet research specifically discussing community leaders’ views on this practice from the perspective of ‘urf in Minangkabau society remains limited. This study aims to analyze the practice of marriage among women pregnant out of wedlock in Nagari Paninggahan, Junjung Sirih Subdistrict, Solok Regency, examine community leaders’ views on this practice, and analyze it from the perspective of ‘urf as one of the considerations in Islamic law. This study used a qualitative approach with a case study design, involving customary leaders, Islamic religious scholars, niniak mamak, bundo kanduang, and community members selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation, and were then analyzed using the interactive analysis technique of Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing. The results show that the practice of marriage among women pregnant out of wedlock in Nagari Paninggahan is carried out as a form of social and customary resolution to preserve family honor, protect women and children, and prevent social conflict within the community. The majority of community leaders support this practice because it is viewed as bringing greater benefit than allowing the problem to develop without resolution. This finding contributes to the development of Islamic family law studies based on local wisdom and broadens understanding of the relationship between custom and Islamic law in Minangkabau society. The conclusion of this study emphasizes the importance of synergy between customary and religious approaches in resolving social problems in society. The practical implications of this study indicate the need to strengthen moral guidance and religious education for the younger generation as a preventive effort against similar social problems.